Policy-based Lending and Poverty Reduction: An Overview of Processes, Assessment, and Options - Richard Bolt; Manabu Fujimura (Asian Development Bank (ADB), 2002)
The Asian Development Bank (ADB) has long addressed ways to reduce poverty in its operations and has now established poverty reduction as its overarching objective. The intensified focus on poverty reduction needs to be addressed in conjunction with questions in development that remain on the agenda, for example, economic structural change (both intersectoral and intrasectoral), industrialization, urbanization, and demographic changes. The general association between economic growth and poverty reduction is well documented. However, the nature of economic growth is influenced by numerous and constantly changing noneconomic factors, which in turn will influence the nature of poverty reducing effects. Influences include a country's resource base, the sectoral composition and structure of the economy, the political and policy environment, the legal and regulatory environment, institutional structures, governance, social structures, and human capital. Combined, these features determine the nature and performance of the economy in aggregate and the economy's sectors, including productivity and equity, resulting in different levels of benefit outcomes for different groups including the poor. A basic strategy in ADB operations has been to enhance reduction of poverty through economic growth. However, the renewed concern under the poverty reduction mandate relates to the distributional impact of economic growth that may not adequately benefit the poor, or in some cases negatively affect the poor. This realization has motivated a global reexamination of the appropriate development policy mix that does not leave the poor behind.
hdl:11540/1919
Keywords: 330; Entwicklungsbank; Entwicklungspolitik; Entwicklungshilfe; Armutsbekämpfung; Wirtschaftliche Anpassung; Entwicklungsländer; Asien